A Study on Network Infrastructure Requirement for Kubang Pasu Land Office - Syarifah Adilah, Mohamed Yusoff (2004)
Phenomenal growth in e-government sectors and the potential of intranet has efficiently centralized the information at local authorities and significantly change the way business is done. The purpose of this study is to propose suitable network diagram and its infrastructure for the Kubang Pasu district land office to implement intranet and extranet services. This study follow ‘Tried and True method' proposes by Lucent Technologies to analyze, identify application portfolio and the level of usage of network for each unit. From this study, the preparations for the network infrastructures are different depend on the system use in the organization and their future planning. Therefore a good planning for the network infrastructure can help in organizing a reliable, expandable and usable network equivalent to government mission in providing e-services through local authorities.